Learning Choreography: An Investigation of Motor Imagery, Attentional Effort, and Expertise in Modern Dance - Carey, Katy; Moran, Aidan; Rooney, Brendan (Frontiers in Psychology, 2019)
The study of choreography in dance offers researchers an intriguing window on the relationship between expertise, imagination and attention in the creative process of learning new movements. The present study investigated an unresolved issue in this field – namely, the effects of expertise on motor imagery (MI; or the mental rehearsal of actions without engaging in the actual movements involved) and attentional effort (as measured by pupil dilation) on dancers while they engaged in the processes of learning, performing and imagining a dance movement. Participants were 18 female dancers (mean age = 23, SD = 5.85) comprising three experience levels (i.e., novice, intermediate and expert performers) in this field. Data comprised these participants’ MI scores as well as their pupil dilation while they learned, performed and imagined a 15 second piece of choreography. In addition, the time taken both to perform and to imagine the choreography were recorded. Results showed no significant effect of dance expertise on motor imagery but some differences between beginners and intermediate dancers in attentional effort (pupil dilation) at the start of the performance and the imagined movement conditions. Specifically, the beginners had the highest pupil dilation, with the experts having the second highest, while intermediates had the lowest dilation. Further analysis suggested that the novice dancers’ pupil dilation at the start of the performance may have been caused, in part, by the initial mental effort required to assess the cognitive demands of the dance task keywords: dance, creativity, expertise, motor imagery, attention, pupillometry